(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Motor skills are closely linked to cognitive functions such as attention, memory, and executive functioning. The findings highlight the need for integrating motor and cognitive training in educational and therapeutic settings for children with autism, potentially improving their long-term developmental outcomes. As a link between TDC and children with abnormal development, the co-occurrence of motor coordination issues and scholastic struggles in DCD children might be seen as a bridge Many developmental diseases share symptoms with cognitive impairments, lending credence to the idea that the two go hand in hand Each participant in the research had their baseline score determined using an evaluation tool called the Cognitive and Social Skill evaluation Test for Children with ASD.